Effect of hydrolysis treatment on cellulose nanowhiskers from oil palm (Elaeis guineesis) fronds: morphology, chemical, crystallinity, and thermal characteristics. - K. Saurabh, Chaturbhuj; Dungani, Rudi; A.F., Owolabi; N.S., Atiqah; Ashaari, Zaidon; N. A., Sri Aprilia; Sarker, Md. Zaidul Islam; H. P. S., Abdul Khalil (NC State University, 2016)
Oil palm fronds biomass was used as a source for isolation of cellulose nanowhiskers (CNW), and its subsequent characterization was done. Non-cellulosic components such a lignin, hemicellulose, and pectin were removed from the biomass by chemimechanical alkaline hydrogen peroxide method followed by sulphuric acid hydrolysis having different time duration of hydrolysis. Apart from the progressive reduction in peaks characteristic of hemicellulose and lignin dissolution, FTIR spectroscopy analysis showed that the hydrolysis did not affect the chemical structure of CNW was revealed by TEM. XRD analysis revealed that the natural structural of cellulose I polymorph was mantained irrespective of the hydrolysis time. High thermal stability and aspect ratio of the extracted CNW demostrated its suitability as a reinforcement material in nanocomposites.